Pseudomonas syringae – Pathogen of Sweet Cherry in Serbia - Gavrilović, Veljko M (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Characteristics of pathogenic Pseudomonas bacterial strains isolated from cherry in Serbia are presented in the article. Two types of symptoms were observed on cherry trees at few localities with intensive production in Serbia (Belgrade, Čačak, Topola, Šabac, Novi Sad). The first symptom is bud necrosis and the second bacterial canker of cherry branch. Gram negative, fluorescent, oxidative bacterial strains were isolated from the margin of necrotic tissue. All investigated strains were levan and HR positive, while negative results were recorded for oxidase, pectinase and arginin dihydrolase tests (LOPAT+- - - +). Based on pathogenicity tests and differential GATT tests, investigated strains were divided in two distinct groups: the first group consisted of strains isolated from necrotic cherry branch which caused necrosis on artificially inoculated cherry, pear and lemon fruits, syringae leaves and bean pods, were gelatin and aesculin positive, and tyrosinase and tartrate negative (typical characteristics of P.s. pv. syringae). Contrary, second group strains were isolated from necrotic cherry buds, showed negative results in mentioned pathogenicity tests, gelatin and aesculin tests were negative, while tyrosinase and tartrate werepositive (typical characteristics of P.s. pv. morsprunorum). REP PCR analyses showed that strains isolated from necrotic cherry buds belong to P. s. pv. morsprunorum compared to referent strain. In contrast, isolates obtained from necrotic cherry branches had unique fingerprint profiles but different from all reference strains. According to the obtained results it was concluded that both pathovars of P. syringae (syringae and morsprunorum) cause necrosis of cherry trees in Serbia.
Keywords: REP PCR; GATT tests; Pathogenicity; Pseudomonas syringae; Cherries